Investigating the Effect of Farm Management, Soil, and Climate on Hop Diastatic Potential. (6th October 2022) - Stokholm, Arnbjørn; Van Simaeys, Karli; Gallagher, Andy; Weaver, Garrett; Shellhammer, Thomas H.
Abstract: To investigate potential sources for field-to-field variation in hop diastatic power, three varieties of hops (Mosaic®, Simcoe®, and Strata®) from harvest year 2019 were collected from different fields managed by a single hop grower throughout the hop growing region within Oregon's Willamette Valley. Fields for this study were selected based on soil type and weather patterns, and eleven fields were identified for sampling (3 Mosaic®, 3 Strata®, and 5 Simcoe®). Farm management data on fertilization rates and pesticide applications were collected by the grower (Coleman Agriculture). Using USGS soil maps, five individual sites within each field were identified for soil sampling, and hop bines near those sites were GPS tagged and hand harvested when they were at similar maturities. After harvest, the hops were analyzed for enzymatic activity using an HPLC method. The relationships between hop enzymatic activity and the farm management, soil, and weather data yielded associations with soil texture, growing degree day accumulation, fertilization practice, and pesticide application. The data also suggest a potential link between hop diastatic power and downy mildew ( Pseudoperonospora humuli ) or powdery mildew ( Podosphaera macularis ) infection. The links between hop diastatic power and agronomic variables will allow farmers to minimize hop creep potential in the hop field thereby potentially mitigating the effects that brewers see in the cellar.